Determining the Gender Differences in Cardiovascular Responses to Isometric Exercise in Normotensive Subjects - Prema Joshi K.; Sunita Handergulle (Highlights on Medicine and Medical Research Vol. 13, 2021)
Introduction: There are various conflicting findings about the influence of gender on effect of isometric exercise on cardiovascular parameters. Aim: The study sought to ascertain gender differences in cardiovascular responses to isometric exercise. Materials and Methods: Handgrip exercises were performed on 25 normotensive females and 25 normotensive males (ages 20-25). The following parameters were studied – i) Maximum voluntary contraction (MVC), ii) Endurance time (ET), iii) Heart rate, systolic blood pressure, diastolic blood pressure and cardiac work was measured before and immediately after the handgrip exercise at 40% MVC. iv) all the above parameters were compared in between males and females. Results: 1) When comparing males and females, MVC was substantially higher in males. 2) Females’ endurance time was shown to be definitely higher than males’. 3) In both males and females, the heart rate, systolic blood pressure, diastolic blood pressure, and cardiac work increased significantly after hand grip training compared to before exercise. Conclusion: Sympathetic activity is accelerated after isometric type of exercise. The responses are greater in males as compared to females.